A new cave-dwelling species of Plakina (Porifera: Homoscleromorpha) from Crete, Greece (South Aegean Sea) - Lage, Anaíra; Araujo, Hannah Paola Mota; Gerovasileiou, Vasilis; Muricy, Guilherme (Zootaxa, 2018)
Recent studies showed a high diversity of the class Homoscleromorpha (Porifera) in the North Aegean Sea. In the South Aegean Sea, however, only one species of the homoscleromorph genus Plakina, P. weinbergi, was reported so far. Here we describe a new species of Plakina from a marine cave in the South Aegean Sea (Crete Island, Greece), viz., Plakina strongylata sp. nov. The new species is white, fragile, with a highly folded surface, and its spicules are diods, triods and calthrops with rounded extremities plus mono- and dilophose diods, mono-, di- and trilophose triods, and mono-, di, tri- and tetralophose calthrops. The number of Plakina species worldwide is raised to 35, of which nine occur in the Aegean Sea.